Pathway towards an ideal and sustainable framework agreement for the public procurement of vaccines in Spain: a multi-criteria decision analysis - N. Zozaya González; B. Alcalá Revilla; P. Arrazola Martínez; J. R. Chávarri Bravo; I. Cuesta Esteve; A. J. García Rojas; F. Martinón-Torres; E. Redondo Margüello; A. Rivero Cuadrado; S. Tamames Gómez; J. Villaseca Carmena; A. Hidalgo-Vega (Taylor & Francis Group, 2020)
Objective: To advance the development of an ideal and sustainable framework agreement for the public procurement of vaccines in Spain, and to agree on the desirable award criteria and their relative weight. Methods: A multidisciplinary committee of seven health-care professionals and managers developed a partial multi-criteria decision analysis to determine the award criteria that should be considered and their specific weights for the public procurement of routine vaccines and seasonal influenza vaccines, considering their legal viability. A re-test of the results was carried out. The current situation was analyzed through 118 tender specifications and compared to the ideal framework. Results: Price is the prevailing award criterion for the public procurement of both routine (weighting of 60% versus 40% for all other criteria) and influenza (36% versus 64%) vaccines. Ideally, 22 criteria should be considered for routine vaccines, grouped and weighted into five domains: efficacy (weighting of 29%), economic aspects (27%), vaccine characteristics (22%), presentation form and packaging (13%), and others (9%). Per criteria set, price was the most important criterion (22%), followed by effectiveness (9%), and composition/formulation (7%). Regarding influenza vaccines, 20 criteria were selected, grouped, and weighted: efficacy (29%), economic aspects (25%), vaccine characteristics (20%), presentation form and packaging (16%), and others (11%). Per criteria set, price was also the most relevant criterion (19%), followed by composition/formulation (8%), and effectiveness (8%). Conclusions: Contrary to the current approach, technical award criteria should prevail over economic criteria in an ideal and sustainable framework agreement for the public procurement of vaccines.